Artificial intelligence in patient education: evaluating large language models for understanding rheumatology literature - Mendoza-Pinto, Claudia; Munguía-Realpozo, Pamela; Etchegaray-Morales, Ivet; Ramírez-Lara, Edith; Solis-Poblano, Juan Carlos; García-Flores, Máximo Alejandro; Ayón-Aguilar, Jorge (Frontiers in Digital Health, 2025)
BackgroundInadequate health literacy hinders positive health outcomes, yet medical literature often exceeds the general population's comprehension level. While health authorities recommend patient materials be at a sixth-grade reading level, scientific articles typically require college-level proficiency. Large language models (LLMs) like ChatGPT show potential for simplifying complex text, possibly bridging this gap.ObjectiveThis study evaluated the effectiveness of ChatGPT 4.0 in enhancing the readability of peer-reviewed rheumatology articles for layperson comprehension.MethodsTwelve open-access rheumatology articles authored by the senior investigators were included. Baseline readability was evaluated utilizing Flesch-Kincaid Grade Level (FKGL) and Simple Measure of Gobbledygook (SMOG) indices. Each article was processed by ChatGPT 4.0 with a prompt requesting simplification to a sixth-grade level. Two expert rheumatologists evaluated the generated summaries’ appropriateness (accuracy, absence of errors/omissions). Readability changes were analyzed using paired t-tests.ResultsChatGPT significantly improved readability (P < .0001), reducing the average reading level from approximately 15th grade (FKGL: 15.06, SMOG: 14.08) to 10th grade (FKGL: 10.52, SMOG: 9.48). The expert reviewers deemed the generated summaries appropriate and accurate. The average word count was significantly reduced from 3,517 to 446 words (P = 0.047).ConclusionsChatGPT effectively lowered the reading complexity of specialized rheumatology literature, making it more accessible than the original publications. However, the achieved 10th-grade reading level still exceeds the recommended sixth-grade level for patient education materials. While LLMs are a promising tool, their output may require further refinement or expert review to meet optimal health literacy standards and ensure equitable patient understanding in rheumatology.